Dohviezdny večer - Ábelová, Mirka, 1985-; Balko, Peter, 1988-; Bodnárová, Jana, 1950-; Dianišková, Veronika, 1986-; Fulmeková, Denisa, 1967-; Futová, Gabriela, 1971-; Hevier, Daniel, 1955-; Hlušíková, Marta, 1952-; Jobus, Branislav, 1969-; Karpinský, Peter, 1971-; Klimáček, Viliam, 1958-; Kompaníková, Monika, 1979-; et al. (Literárne informačné centrum, 2021)
Dvadsaťpäť príbehov o vianociach.